(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2021)
In spring of 2020, as the coronavirus spread across the world and governments dithered over what to do, I began talking with my co-workers about unionising our office. We work as journalists at a New York-based media company, and the last time we faced a major global crisis, executives throughout our industry fired a record number of people to keep profits up. I believed they would likely do the same this time around (they did) and that we would be better protected if we organised. Workers in the United States enjoy few protections. In most cases, we can be fired at will, which is a frightening prospect sharpened further by the fact that our ticket to modern medicine is usually through employer-provided health insurance. Practically speaking, if you lose your job in the allegedly freest country in the world, you lose your doctor. A frightening prospect in a pandemic. I wanted to understand whether anyone else believed, as I did, that if we consolidated our individual power, we would better withstand the economic fallout of Covid-19. Through collective bargaining, we could potentially prevent mass layoffs, or at least codify stipulations for severance, and resolve the issues we’d faced at work prior to the pandemic, too. What follows describes and reflects on the process I took with my co-workers to unionise our office, which I believe serves as an example of how community building intersects with trade unionisation, because both rely on one-to-one relationships between individuals. My hope is that it contributes to the demystification of the unionisation process and offers one potential starting point for others who want to unionise their workplaces. I believe that’s an urgent need for our modern era, in which a new billionaire is minted more frequently than daily , while the rest of us get scraps.